Systematic Review: The Relationship Between Environmental Sanitation and the Incidence of Stunting - Kirana, Tharisya Ayu; Hasyim, Hamzah; Sunarsih, Elvi (Newinera Publisher, 2024)
Stunting in children under five is a crucial public health issue in developing countries, including Indonesia. Poor environmental sanitation has been identified as a significant factor influencing the incidence of stunting. This study aims to review the latest literature linking environmental sanitation conditions with the prevalence of stunting. The method used in this research is a literature review, utilizing several research articles from the past five years obtained from various scientific journal sources. The type of study is an observational analytic survey with a case-control design. The research was conducted by comparing two groups: cases and controls. Based on the literature review, poor environmental sanitation, particularly access to clean water and adequate sanitation facilities, has a significant relationship with the high prevalence of stunting in children across various countries. Providing clean water, proper sanitation facilities, and hygiene education programs have been proven to reduce stunting rates. Improving access to environmental sanitation and hygiene is a critical step in reducing the prevalence of stunting. Sanitation interventions should be a priority in public health programs in developing countries.